Coastal Food Diversification via Remang Fish (Muraenesox cinereus) Amplang: Effects of Tapioca Starch-to-Remang Fish Flesh Ratio on Hardness, Chemical, Microbiological, and Sensory Characteristics - Hanidah, In-In; Moody, Sumanti Debby; Huda, Syamsul; Suryawardana, Ameera Xaviera Sakinah; Utami, Annisa Ratri (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractSmall-scale fisheries supply local raw materials with potential for coastal food diversification. Remang fish (Muraenesox cinereus) offers opportunities as a raw material for value-added amplang that has not been widely processed. This research assessed the ratio effect of tapioca starch-to-remang fish flesh on physical, chemical, microbiological, and sensory quality and its compliance with SNI 7762:2013. A randomized complete block design experiment on 3 formulations (70:30, 60:40, 50:50) with 4 replications included proximate tests, hardness tests, total plate counts, Escherichia coli, and sensory tests by 23 panelists using a 7-point scale assessment. The moisture content of 1.07% – 2.29% and ash of 2.77% –3.92% were below the threshold, the protein content of 7.87% – 10.95% exceeded the minimum limit, the total plate count was 2.2 log CFU/g – 3.2 log CFU/g, and Escherichia coli was negative. Meanwhile, the hardness decreased from 2,737.79 gForce to 268.66 gForce as the fish portion increased. The 50:50 formulation achieved the highest sensory score, but the fat content of 51.18% exceeded the 35% limit, while the fat content of the 70:30 and 60:40 formulations was within the limits of 17.08% and 23.36%. The findings confirm the suitability of remang fish as a raw material for amplang. Oil absorption control and high-barrier packaging are needed to ensure sensory excellence in line with quality compliance. These study results can be used as a basis for coastal food diversification based on local resources and commercialization opportunities for micro, small, and medium enterprises.Keywords: coastal food diversification, remang fish amplang, sensory quality, tapioca starch-to-fish flesh ratio AbstrakPerikanan skala kecil menyuplai bahan baku lokal yang berpotensi untuk diversifikasi pangan pesisir. Ikan remang (Muraenesox cinereus) menawarkan peluang sebagai bahan baku amplang bernilai tambah yang belum banyak diolah. Riset ini menilai pengaruh rasio tapioka terhadap daging ikan remang pada mutu fisik, kimia, mikrobiologi, dan sensoris dan kesesuaiannya dengan SNI 7762:2013. Eksperimen randomized complete block design pada tiga formulasi (70:30, 60:40, 50:50) dengan 4 ulangan mencakup uji proksimat, uji kekerasan, angka lempeng total, Escherichia coli, dan uji sensori oleh 23 panelis menggunakan penilaian skala 7 poin. Kadar air 1,07–2,29% dan abu 2,77–3,92% berada di bawah ambang batas, protein 7,87–10,95% melampaui batas minimum, angka lempeng total 2,2–3,2 log CFU/g dan Escherichia coli negatif, sedangkan kekerasan turun dari 2.737,79 gForce menjadi 268,66 gForce seiring kenaikan porsi ikan. Formulasi 50:50 meraih skor sensori tertinggi, tetapi kadar lemak 51,18% melampaui batas 35%, sedangkan kadar lemak formulasi 70:30 dan 60:40 berada dalam batas 17,08% dan 23,36%. Temuan menegaskan kelayakan ikan remang sebagai bahan baku amplang. Pengendalian serapan minyak dan high-barrier packaging dibutuhkan agar keunggulan sensori sesuai dengan kepatuhan mutu. Hasil penelitian ini dapat menjadi dasar diversifikasi pangan pesisir berbasis sumber daya lokal dan peluang komersialisasi bagi usaha mikro, kecil, dan menengah.Kata kunci: amplang ikan remang, diversifikasi pangan pesisir, mutu sensoris, rasio pati tapioka terhadap daging ikan